Bacterial indicators of environmental stress in the gut microbiome of free-ranging European roe deer inhabiting agricultural landscapes - Rafał Łopucki; Ewa Sajnaga; Kinga Ożga; Dagmara Stępień-Pyśniak; Arkadiusz Jastrzębski; Marcin Świątek; Marta Kloch; Ilona Sadok; Paweł Nasiadka; Petter Kjellander; Daniel Klich (Scientific Reports)
Abstract Environmental stressors can influence the gut microbiota of wild ruminants, yet their effects in free-ranging populations remain poorly understood. This study examined associations between physiological stress and gut microbiota composition in free-ranging European roe deer (Capreolus capreolus) from agricultural landscapes in central Poland. Fecal samples from 54 legally hunted individuals were analyzed for cortisol metabolite concentrations and bacterial community composition using 16S rRNA gene sequencing. Cortisol metabolite levels ranged from 17.9 to 371.4 ng ml⁻¹, allowing classification into low- and high-stress groups. Alpha diversity metrics did not differ between groups, but beta diversity analyses revealed significant differences in microbial community structure linked to stress. Stress remained a significant predictor of microbiota composition even after adjusting for confounding variables such as area and season, with its effect varying by context. Ratios of Christensenellaceae to Rikenellaceae, Bacteroidaceae and Prevotellaceae were significantly elevated in the high-stress group, indicating potential as microbial biomarkers of physiological stress. Additionally, Barnesiellaceae and Succinivibrionaceae (families involved in immune modulation and fermentation) were depleted under higher stress conditions. These findings highlight the role of gut microbiota in responses to environmental stressors and suggest that microbial signatures could serve as biomarkers for assessing the impact of agriculture on wildlife health and ecosystem stability.